DARKEST TIME OF BELLA'S LIFE AND ITS INFLUENCE ON HER PERSONALITY IN STEPHENIE MEYER'S NEW MOON: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HIDAYATI, SITI NUR (2011)
The objective of the study is to examine how darkest time of Isabella Swan influence her personality is reflected in Stephenie Meyer's New Moon based on individual psychological approach and the structural elements. The research is conducted by using qualitative method. The object of the research is the novel entitled New Moon written by Stephenie Meyer. The writer uses two data sources namely primary and secondary data source. The primary data is novel New Moon written by Stephenie Meyer. The secondary data sources are the other sources related to the analysis like some books and internet. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The results of the research are as follows: first, based on the structural analysis in this novel, it is coherence to each other. Stephenie Meyer wants to convey a moral message that love can be possessed by all creatures without differentiating world and with love everything is full of peace. Second, based on individual psychological analysis of this novel, it is evident that every human needs love in her life and if she lives without love, her life becomes dark. In this novel, Isabella Marie Swan becomes lonely about her love problem in her life; she just wants to live with her boyfriend.